Advances in Manufacturing - Hamrol, Adam.; Ciszak, Olaf.; Legutko, Stanisław; Jurczyk, Mieczysław; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book covers a variety of topics in material, mechanical, and management engineering, especially in the area of machine design, product assembly, measurement systems, process planning and quality control. It describes cutting-edge methods and applications, together with exemplary case studies. The content is based on papers presented at the 5th International Scientific-Technical Conference (MANUFACTURING 2017) held in Poznan, Poland on 24-26 October 2017. The book brings together engineering and economic topics, is intended as an extensive, timely and practice-oriented reference guide for researchers and practitioners, and is expected to foster better communication and closer cooperation between universities and their business and industry partners. .
Keywords: Engineering design; Manufactures; Production management; Industrial Management; Computer-aided engineering; Engineering Design; Machines, Tools, Processes; Production; Industrial Management; Computer-Aided Engineering (CAD, CAE) and Design